Model Pendidikan Kewarganegaraan Sebagai Pembelajaran Moral Dan Karakter - Nurdiansyah, Edwin; Aulia Novemy Dhita (University of Muhammadiyah Malang, 2024)
Citizenship education which is often identified with moral and character education is very interesting to study, especially regarding appropriate learning models to be applied in the learning process. This study aims to provide an argumentative description of civics education as a way of learning morals and character. This research was carried out using a qualitative approach through literature studies. Data analysis focused on data reduction, data display and drawing conclusions. The results of this study indicate that moral and character learning must be carried out by prioritizing critical thinking skills, one of which can be through Habermas' emancipatory questions, that is why civics education must be carried out with a dialogical approach through critical pedagogy so can make realize moral and character actions in accordance with which are expected.